The future prospect for religious dialogue in Malaysia - Khadijah Mohd. Khambali@Hambali; Suraya Sintang; Alwani Ghazali; Rahimin Affandi Abdul Rahim; Romzi Ationg; Nur Farhana Abdul Rahman; Syamsul Azizul Marinsah; Halina Sendera Mohd. Yakin; Mohd. Nazmi Mohd. Khalli (Pennwell Corporation, 2020)
Basically this article gives primary focus on the religious dialogue in Malaysia. Most importantly, the focal study is on the prospect issues of future trends for the religious dialogue in Malaysian global context. Initially, this article highlights the issue of the religious dialogue in the contemporary Malaysia which has been designed to be divided into several sections and discussions by content analysis. We get to witness how religious dialogue process had been conducted in Malaysian context even though there are still many flaws that need to be fixed together by both sides, the Muslims and non-Muslims. By using futuristic analytical approach (examining current trends and proposing alternative solutions), this paper argues that the religious dialogue can be a future prospect of problem solving for modern crisis and therefore, an urgent need for global agenda. Religious dialogue are now expanding in Malaysia as the people from different religions typically practise several kinds of dialogues such as dialogue in life, dialogue through acting out together and dialogue through intellectual discourse. Having through these practical life experience in dialogue, it is believe that the religious dialogue trend in Malaysia has a somewhat bright future and proven to be in reality with several supports. The support to introduce the subject of religious pluralism concept from the Islamic perspective on the discipline of civilizational dialogue to be studied by all devotees of world religions. Most importantly, creating a framework for Islamic discipline of knowledge that is related to the concept of religious pluralism in middle form which has to be the opposite of secularist approach of anti-Islamic tradition. This paper conclude that the bright future of religious dialogue, while many shortcomings still need to be addressed together on both sides; Muslim and non-Muslims, has become a reality in Malaysia.